2019
DOI: 10.4185/rlcs-2019-1347
|View full text |Cite
|
Sign up to set email alerts
|

Método para la construcción de grandes corpus temáticos de noticias de prensa digital. Hacia un corpus sobre el hecho alimentario

Abstract: Método para la construcción de grandes corpus temáticos de noticias de prensa digital. Hacia un corpus sobre el hecho alimentario Method for the construction of large thematic corpora of online news articles. Towards a corpus of food-related news

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
1
Order By: Relevance
“…The analysis units for the present study were identified from a previously constructed corpus of food-related news items published by emol.com, latercera.com, and elmostrador.cl in 2016 [ 76 ]. The rationale, method and results of this already constructed corpus on food in general were published in 2019 in English (translated version) [ 76 ] and Spanish (original version) [ 77 ]. A custom dictionary was built on anthropological and sociological works by a process of conceptualization of the food fact and, then, its operationalization into a list of keywords that, due to their properties, uses, and semantic meanings, are representative of the food phenomenon and operative for empirical work.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis units for the present study were identified from a previously constructed corpus of food-related news items published by emol.com, latercera.com, and elmostrador.cl in 2016 [ 76 ]. The rationale, method and results of this already constructed corpus on food in general were published in 2019 in English (translated version) [ 76 ] and Spanish (original version) [ 77 ]. A custom dictionary was built on anthropological and sociological works by a process of conceptualization of the food fact and, then, its operationalization into a list of keywords that, due to their properties, uses, and semantic meanings, are representative of the food phenomenon and operative for empirical work.…”
Section: Methodsmentioning
confidence: 99%
“…Los datos obtenidos se sometieron a un doble procedimiento (Sánchez, del Valle y Mensa, 2019): 1) seleccionar la columna de URL y comprobar que no existían resultados duplicados y 2) verif icar que las publicaciones compiladas atendían a los criterios fijados (f ec ha, palabras clave, etc.) y no había falsos positivos.…”
Section: Verif Icación De Los Datos Obtenidos Y Almacenamientounclassified
“…This interest, however, has not been reflected in the literature on media analysis. Although for the last decade there have been several studies on how the media address health and food issues (Marí ñ-Murilló et al, 2016;Fu ster et al, 2009;Varela Sua rez et al, 2020), food security (Marí ñ-Murilló, et al, 2015;Elika, 2016) and other issues like obesity (Westall, 2010), there are hardly any studies on how the media have covered the issue of food deprivation in a context of increasing precariousness (Sa ñchez Sabate et al, 2019). Some studies did analyze this issue within the framework of agenda setting, and more particularly framing theory (Marí ñ-Murilló et al, 2020).…”
Section: Introductionmentioning
confidence: 99%